Microbiota and Probiotics: The Role of Limosilactobacillus Reuteri in Diverticulitis - Andrea Piccioni; Laura Franza; Vanessa Vaccaro; Angela Saviano; Christian Zanza; Marcello Candelli; Marcello Covino; Francesco Franceschi; Veronica Ojetti (Medicina, 2021)
The microbiota is the set of commensal microorganisms, residing in the organism, helping proper functioning of organs and systems. The role that the microbiota plays in maintaining the health of vertebrates is widely accepted, particularly in the gastrointestinal system, where it is fundamental for immunity, development, and conversion of nutrients. Dysbiosis is an alteration of the microbiota which refers to a disturbed balance, which can cause a number of pathologies. Probiotics have proven to be effective in modulating the microbiota of the gastrointestinal system and, therefore, in promoting the health of the individual. In particular, Lactobacilli are a group of Gram-positive bacteria, which are able to produce lactic acid through glucose metabolism. They are present in different microenvironments, ranging from the vagina, to the mouth, to different tracts of the small intestine. In the present review, we will discuss the use of Limosilactobacillus in human health in general and more specifically in diverticulitis. In particular we analyze the role of Limosilactobacillus reuteri and its anti-inflammatory action. For this review, articles were identified using the electronic PubMed database through a comprehensive search, conducted by combining key terms such as “diverticulitis”, “Limosilactobacillus reuteri”, “human health and disease”, “probiotics”. We selected all the articles published in the last 10 years and screened 1017 papers. Articles referenced in the screened papers were evaluated if considered interesting for our topic. Probiotics have proven to be effective in modulating the microbiota of the gastrointestinal system and, therefore, in promoting the health of the individual. The importance of probiotics in treating diverticular disease and acute diverticulitis can be further understood if taking into consideration some pathophysiological aspects, associated to the microbiota. L. reuteri plays an important role in human health and disease. The effectiveness of L. reuteri in stimulating a correct bowl motility partly explains its effectiveness in treating diverticulitis. The most important action of L. reuteri is probably its immunomodulating activity. Levels of IL-6, IL-8, and Tumor necrosis factor (TNF-alpha) are reduced after supplementation with different strands of Lactobacilli, while T-regulatory cells increase in number and activity. Anyway, new mechanisms of action of probiotics come to light from the many investigations currently taking place in numerous centres around the world and to improve how exactly probiotic administration could make the difference in the management of diverticular disease and acute diverticulitis.